The Effect of Flipped Classroom Assisted by Edpuzzle and PhET Simulation on Students’ Critical Thinking Skills in Electrochemistry - Fitriyanti Ahmad; Masrid Pikoli; Erni Mohamad; Mangara Sihaloho; Thayban Thayban; Erga Kurniawati; La Alio (Universitas Negeri Gorontalo, 2026)
Students’ critical thinking skills, particularly in electrochemistry, remain low because instruction tends to be teacher-centered and makes insufficient use of interactive technology. In addition, studies investigating the use of the flipped classroom approach assisted by Edpuzzle and PhET simulations in electrochemistry learning remain scarce. Therefore, this research was conducted to examine the impact of applying a flipped classroom model integrated with Edpuzzle and PhET simulations on students’ critical thinking skills. The study used a quasi-experimental method with a non-equivalent control group design. The research sample consisted of 12th-grade students at SMA Negeri 2 Limboto, selected through purposive sampling. The research instrument consisted of a 10-item essay test that was valid and reliable, with a Cronbach’s Alpha value of 0.814. The results showed that the average critical thinking ability of students in the experimental class increased from 29.17 to 74.26, with an N-Gain value of 0.63, classified as moderate. The Wilcoxon Signed-Rank test showed a significant difference between the pretest and posttest in both classes (p < 0.05), while the Mann–Whitney U test showed no significant difference in the pretest (p = 0.060 > 0.05), but a significant difference in the posttest (p < 0.05). Thus, the flipped classroom model supported by Edpuzzle and PhET simulations can serve as an alternative learning approach to enhance students’ critical thinking skills in electrochemistry.